2021
DOI: 10.1177/13670069211000850
|View full text |Cite
|
Sign up to set email alerts
|

A deliberate language policy or a perceived lack of agency: Heritage language maintenance in the Polish community in Melbourne

Abstract: Aims: By applying the tripartite framework of family language policy, this study seeks to gain insight into heritage language maintenance of Polish families in Melbourne. To this end, an integrative investigation of family language policy encapsulating the heritage language perceptions, practices and management will be employed. Methodology: Based on the data collected through the online questionnaire supplemented with in-depth interviews, quantitative and qualitative analyses have been conducted to obtain a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 78 publications
(89 reference statements)
1
11
0
Order By: Relevance
“…He further postulated the crucial influence of parents' educational background in deciding on what language their children will be raised in. Similar findings were also found in the Acehnese context (Aziz et al, 2021;Fakhrurrazi, 2016;Yusuf et al, 2022), and some other previous studies in different language contexts (Gupta, 2020;Kheirkhah & Cekaite, 2015;Romanowski, 2021).…”
Section: Parents' Attitudes and Language Shiftsupporting
confidence: 89%
See 2 more Smart Citations
“…He further postulated the crucial influence of parents' educational background in deciding on what language their children will be raised in. Similar findings were also found in the Acehnese context (Aziz et al, 2021;Fakhrurrazi, 2016;Yusuf et al, 2022), and some other previous studies in different language contexts (Gupta, 2020;Kheirkhah & Cekaite, 2015;Romanowski, 2021).…”
Section: Parents' Attitudes and Language Shiftsupporting
confidence: 89%
“…This is what has been concerned by Anderbeck (2012) that, nowadays, parents heavily rely on the environment for their children to learn their heritage language. Consequently, less intention of parents to speak Acehnese to their children has put the position of this language to be unsafe because Acehnese children are not able to speak it fluently as what has been found in several previous studies (Fakhrurrazi, 2016;Gupta, 2020;Ismail et al, 2021;Kheirkhah & Cekaite, 2015;Romanowski, 2021;Zhu et al, 2020). Ewing (2014) has also acknowledged that today, the traditional pattern of learning the heritage language has been disturbed among children because they no longer learn their heritage language from their parents in their homes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The low efficacious learners tend to avoid challenging or interactive L2 experiences, thus withdrawing from the acquisition and language maintenance process despite potentially having abilities or previous performance successes. Studies have shown how language self-efficacy negatively correlates with apprehension and performance avoidance (Pajares & Valiante, 2001), and more importantly, is emerging as a potential contributing factor in language attrition and maintenance (Romanowski, 2021). Graham (2006) has demonstrated how low efficacy language learners tend to make negative attributions to their academic outcomes, often claiming the language learning environment is uncontrollable and inaccessible, creating overall global assumptions of attrition.…”
Section: The Irish Language Contextmentioning
confidence: 99%
“…Positive attitudes and beliefs towards the use, maintenance and transmission of the heritage language, interventions, planning, management, language choices and communication patterns, language ideologies, socio-political factors, language status and prestige, the size of the immigrant/minority community, linguistic and cultural identities, child and parental agency and emotions, family language socialisation are reflected in explicit and implicit FLPs. Furthermore, such factors as parental education, socio-economic status and prior language-learning experiences, as well as the broad social and cultural context of family life should be taken into consideration (Curdt-Christiansen, 2014Guardado, 2018;King & Fogle, 2013;Romanowski, 2021;Spolsky, 2012).…”
Section: Introductionmentioning
confidence: 99%